Shear behavior of lightweight self-consolidating reinforced concrete beams without transverse reinforcement - Garcia,Sergio Luis González (2020)
Abstract This article investigates the shear behavior of reinforced concrete beams without transverse reinforcement. Two types of concrete were produced: a Reference Conventional Concrete (RCC) and a Lightweight Self-Consolidating Concrete (LSCC), all with an average 28-day compressive strength (fc) of approximately 30 MPa and characterized by rheological and mechanical tests. Twelve 15 x 30 x 200 cm beams were manufactured for shear failure during a four-point bending test. Concrete properties, longitudinal reinforcement ratios (0.89%, 1.27% and 1.68%) and shear-span to depth ratio (1.87 to 2.71) were determined. The studied beams were compared in terms of cracking pattern, diagonal cracking load, shear strength, specific concrete and longitudinal reinforcement deformation at failure. The strength values obtained experimentally were compared with ABNT NBR 6118 (2014), ACI 318 (2019) and CEN EC-2 (2004). The tested beams of LSCC showed less shear strength when compared to beams of RCC.